Reducing Pain and Promoting Healing in Acute Anal Fissure with Individualised Homoeopathic Treatment: A Case Series - Dixit, Ashish Kumar; Yadav, Moorat Singh (Homœopathic Links, 2023)
Anal fissure (AF) is a prevalent cause of severe anal pain and is among the most common anorectal issues encountered in clinical practice. This case series aims to evaluate the effectiveness of individualised homoeopathic medicine (IHM) prescriptions in patients with acute AF. The study included seven diagnosed cases of AF that were treated with personalised homoeopathic medicine. Pain was evaluated using a visual analogue scale (VAS), and the Outcome in Relation to Impact on Daily Life (ORIDL) score was used to assess treatment outcomes and fissure healing at baseline and during follow-up visits. The Modified Naranjo Criteria were used to evaluate the causal attribution of treatment effects. All seven cases showed a significant reduction in VAS scores from baseline to 3 months (mean score: 8.71 ± 0.95 to 0.143 ± 0.37) and ORIDL score at 1 to 3 months for main complaints and overall well-being was from 2.00 ± 0.00 to 3.00 ± 0.00, and 3.71 ± 0.756 to 3.85 ± 0.37 respectively. Complete healing of the fissure was observed in six cases, while partial healing was noticed in one case. The mean Modified Naranjo Criteria score was 8.71 ± 0.75. Therefore, IHM is useful in reducing pain and promoting healing of acute AF, but more research is needed to validate its efficacy with robust methodology. Additionally, future studies should also investigate the role of Paeonia in treating AF. Nonetheless, the findings offer a potential opportunity to improve treatment options for individuals with this painful condition.
Keywords: anal fissure; fissure in ano; individualised medicine; homoeopathy